Women as Phenomena and Men as Sensors in Women’s Magazines - Kandel, Mukti Nath (BMC Journal of Scientific Research, 2018)
This article is an attempt to examine the process of constructing gender roles in society through the women’s magazines. As its title suggests, it examines how female participants, from Nari (e-kantipur publication) have been projected as objects of male gaze (phenomena) and males as the agents of gaze (sensors). Even though such magazines are labeled as “women’s magazines,” the agenda setter and the gatekeeper are certainly the males since the female represented participants are prepared hegemonically to satisfy the male desire. The paper concludes that women are largely depicted and assigned to play four gender stereotyped roles: home decorators, child nurturers, cooks, and persons whose attention is always drawn to their bodies away from their minds.